Tindak Tutur Perlokusi dalam Iklan Sprite Campaign #NyatanyaNyegerin dan Implementasinya sebagai Materi Ajar Teks Iklan, Slogan, dan Poster di SMP - Rohmah, Qotrul Ainiyah (Kajian Bahasa dan Sastra (KABASTRA), 2024)
This research is motivated by Sprite advertisements with advertising phenomena that have perlocutionary speech acts in the narrator's speech. Sprite advertisements are widely aired on television, Sprite advertisements in the hashtag #nyatanyanyegerin there are perlocutionary speech acts. Sprite ads with these hashtags can be accessed via Youtube. The research aims to describe the form and function of perlocutionary speech acts in Sprite advertisements. This type of research is qualitative descriptive. The method used is listening method and note taking technique. This research uses commensurate method and PUP technique to analyze the data. The findings of this study are the form and function of perlocutionary speech acts in the speech of the narrator of Sprite advertisements. The results of the analysis of the form of perlocutionary speech acts in Sprite advertisements consist of: The functions of perlocutionary speech acts in Sprite advertisements include: representative speech acts of recognition, directive speech acts of suggestion, directive speech acts of invitation, directive speech acts of request, expressive speech acts of innuendo, and commissive speech acts of offer.